Vitamin D status and predictors of serum 25-hydroxyvitamin D concentrations in Western Australian adolescents - Black, Lucinda; Jacoby, P.; Burrows, S.; Oddy, W.; Beilin, L.; She Ping-Delfos, W.; Marshall, C.; Holt, P.; Hart, P.; Mori, Takeshi (Cambridge University Press, 2014)
Despite the importance of skeletal growth during adolescence, there is limited research reporting vitamin D status and its predictors in adolescents. Using prospective data from the Western Australian Pregnancy Cohort (Raine) Study, we investigated vitamin D status and predictors of serum 25-hydroxyvitamin D (25(OH)D) concentrations in adolescents. Serum 25(OH)D concentrations were measured in the same participants at 14 and 17 years (n 1045 at both time points). The percentage of adolescents with serum 25(OH)D concentrations < 50, 50–74·9 and ≥ 75 nmol/l was reported year-round and by month of blood collection. We examined the predictors of serum 25(OH)D concentrations, including sex, race, month of blood collection, physical activity, BMI, family income, and Ca and vitamin D intakes (n 919 at 14 years; n 570 at 17 years), using a general linear mixed model. At 14 years, 31 % of adolescents had serum 25(OH)D concentrations between 50 and 74·9 nmol/l and a further 4 % had concentrations < 50 nmol/l. At 17 years, 40 % of adolescents had serum 25(OH)D concentrations between 50 and 74·9 nmol/l and 12 % had concentrations < 50 nmol/l. Caucasian ethnicity, being sampled at the end of summer, exercising more, having a lower BMI, a higher Ca intake and a higher family income were significantly associated with higher serum 25(OH)D concentrations. The proportion of adolescents with serum 25(OH)D concentrations < 50 nmol/l was low in this Western Australian cohort. There is a need for international consensus on defining adequate vitamin D status in order to determine whether strategies to increase vitamin D status in adolescents are warranted.